Effect of the connector thickness on fracture resistance in laminate veneers retained bridges : a three-dimensional finite element analysis - Ahmed, Ahmed Elsayed Mohamed İbrahim (My University, 2019)
Amaç: Bukkal yüzeyde hazırlanan lamina vener destekli tam seramik RBFDP’nin klinik başarısı, yapılan araştırmaların yetersizliğinden dolayı tam olarak bilinmemektedir. Bu çalışmanın amacı, alt kesici dişler üzerinde farklı konnektör kalınlığına sahip lamina vener destekli köprülerde könnektör kalınlığının kırılma direnci üzerindeki etkisini değerlendirmektir.Materyal ve Metot: Alt çene periodontal ligament yapısına sahip, alt sağ orta ve sol yan kesici dişi içeren üç boyutlu sonlu elemanlar analiz modeli hazırlandı. Daha sonra, farklı konnektör kalınlığına sahip (1 mm kannektör kalınlığı grubu ve 2 mm konnektör kalınlığı grubu) üç üyeli lamina vener destekli köprüden oluşan 2 grup oluşturuldu. Yapıştırıcı siman kalınlığı her iki grupta da aynı hazırlandı. Her iki gruba da ısırma kuvvetlerini taklit edecek 100 N'luk yük 3 üyeli köprülerin gövdeleri üzerine bukkal yüzden 45 derecelik açı ile uygulandı. Kırılma kuvvetleri karşılaştırıldı.Bulgular: Konnektör kalınlığı 2 mm olan gruptaki gerilim kuvvetleri, 1 mm konektör kalınlığına sahip gruba göre daha düşük değerler elde edildi.Sonuç: Bu çalışmanın klinik sonucuna göre, 2 mm konnektör kalınlığına sahip üç üyeli RBFDP'lerin, 1 mm konektör kalınlığına sahip olan RBFDP'ler den daha güvenilir olduğu sunucuna varılmıştır. Bukkal yüzde hazırlanan lamina destekli köprüler hem estetik hem de dayanıklılık açısından tercih edilebilirler.

Aim: Laminate retained all-ceramic RBFDP’s clinical success is unknown due to lack of insufficient studies about them. The purpose of this study is to evaluate the Effect of the connector thickness on fracture resistance in laminate veneers retained bridges in the lower central incisor region via finite element method.Material and Method: A three-dimensional finite element analysis model will be developed including mandible, prepared lower right central and left lateral incisor with periodontal ligament structures. Then a 2 groups of a three unit buccally retained laminate veneer bridge was virtually constructed with different thickness of connector a (1mm connector thickness group and 2mm connector thickness group), also a uniform thickness was designed for cement. A load of 100 N applied to the buccal surface at 45 degree, 2mm below the incisal edge of the pontic on both 2 groups three unit to stimulate biting force. The results were compared.Findings: Stresses on connector in the 2mm connector group is lower than stresses on connector in the 1mm connector thickness group. Results: clinical significance of this study shows three unit (double abutments) buccally-retained RBFDPs with 2mm connector thickness are more reliable than three unit (double abutments) buccally-retained RBFDPs with 1mm connector thickness since main reported failure of RBFDPs are in connector areas. The advantage of using buccally retained RBFDPs is more retentive enamel area for cement and higher esthetic outcome.
Lamina vener destekli köprülerde konnektör kalınlığının, kırılma direncine etkisi : üç boyutlu sonlu elemanlar analizi
Keywords: buccally-retained RBFDPs; FEA; Konnektör; Lamina vener; Prosthodontics; Prostodonti; Sonlu Elemanlar Analizi laminates